Penglibatan Wanita Sebagai Subjek Pengiklanan Menurut Perspektif Hukum Islam: Women’s Involvement As A Subject Of Advertising From Islamic Ruling Perspective - Karim, Ayunni; Abdul Rahman, Noor Naemah; Ramli, Mohd Anuar (Online Journal of Research in Islamic Studies, 2018)
Advertising is a medium for promoting goods and services whether verbal or visual. Among the major players in the advertising industry are women, namely managers, models, photographers and the like. In this study, the researcher focused only on the involvement of women as the subject of advertising. Basically, the discussion of this study covers the form of women’s portrayal in current advertising as well as analysis of Islamic ruling regarding the involvement of women in advertising. To achieve these objectives, this research is carried out qualitatively by utilizing library research. The finding shows that the portrayal of women as one of the subjects in advertising has raised issues of sexual exploitation, as well as stereotyping, sexual harassment, degrading dignity, immorality and tabarruj. Based on issues arising from the portrayal of women in an advertisement, some criteria set in Islam should be followed, e.g. the work or activity involved is not prohibited in Islam and Muslim women should abide the rule in doing outdoor activities such as dressing, walking, speaking, appearance and attitude. It aims to preserve the rights, position and dignity of women involved in advertising and indirectly proves that Islam is a religion which promotes women’s dignity and preserves their glory.